CYTOTOXICITY TEST OF N-HEXANE, ETHYL ACETATE, AND WATER FRACTIONS FROM THE ETHANOL EXTRACT OF SENDUDUK LEAVES (Melastoma malabathricum L.) ON MCF-7 CELLS USING THE MTT ASSAY METHOD - Tri Oktarina; Peni Indrayudha; Rima Munawaroh (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
The world's richest flora may be found in Indonesia, where a variety of plants, such as the sesame plant (Melastoma malabathricum L) or MM, may be used to treat cancer. According to earlier studies, the methanol extract of the leaves had a substantial anticancer effect on the MCF-7 cell line, with an IC50 of 7.14 µg/mL. The purpose of this study was to evaluate the cytotoxic potential of the water, ethyl acetate, and n-hexane fractions of senduduk leaf ethanol extracts. Maceration was the extraction technique, partitioning (liquid-liquid extraction) was the fractionation technique, and the MTT method was employed to assess cytotoxic activity. The n-hexane, ethyl acetate, and water fractions showed cytotoxic effects with IC50 values of 137.200 µg/mL, 17.108 µg/mL, and 610.863 µg/mL, respectively. The water and n-hexane fractions were classified as fragile, based on the results of the cytotoxicity test. The ethyl acetate fraction, on the other hand, was added to the active category for suppressing MCF-7 cells.  Keywords: Melastoma malabathricum L, Cytotoxic, Cells, MCF-7, MTT assay